Kualitas Layanan dan Kepuasan Jamaah Masjid melalui Pendekatan Model SERVQUAL - Mujahidin, Tafaul; Wibowo, Hari Santoso; Masrukan, Fathurrahman (Tadbir: Jurnal Manajemen Dakwah, 2025)
This study aims to analyze the effect of service quality on mosque congregational satisfaction using the SERVQUAL model. This research approach is quantitative. The study sample consisted of 120 respondents, and data analysis was performed using SmartPLS version 3.0. The results show that service quality significantly affects congregational satisfaction with an R² value of 0.6677. The dimensions of tangible, reliability, and responsiveness have a positive and significant influence, while assurance and empathy have no effect. The responsiveness dimension is the dominant factor in shaping congregational satisfaction, which emphasizes the importance of the mosque management's promptness and speed in providing services